2020
DOI: 10.1364/boe.387252
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of movement artefacts in handheld laser speckle contrast perfusion imaging

Abstract: Functional performance of handheld laser speckle contrast imaging (LSCI) is compromised by movement artefacts. Here we quantify the movements of a handheld LSCI system employing electromagnetic (EM) tracking and measure the applied translational, tilt and on-surface laser beam speeds. By observing speckle contrast on static objects, the magnitudes of translation and tilt of wavefronts are explored for various scattering levels of the objects. We conclude that for tissue mimicking static phantoms, on-surface sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…4 f). In a previous study, the average on-surface speed for handheld measurements by 10 healthy operators on a static object was calculated as 9 mm/s where the measurement distance was 20 cm 18 . In this study, the calculated value is 12.7 mm/s with the measurement distance of 40 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 f). In a previous study, the average on-surface speed for handheld measurements by 10 healthy operators on a static object was calculated as 9 mm/s where the measurement distance was 20 cm 18 . In this study, the calculated value is 12.7 mm/s with the measurement distance of 40 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Left, a front view of the handheld probe. Middle, handheld probe without a cap (reprinted from 18 ). Right, schematic drawing of the handheld probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to model movement artefact so that their occurrence can be prevented and/or compensated. In other studies, we experimentally showed that movement artefacts caused by translation depend on the optical properties of the medium [9] as well as the type of illumination [10]. In this work, we use the concept of optical Doppler effect to predict speckle contrast drop due to linear motion, and for static objects.…”
Section: Introductionmentioning
confidence: 92%
“…Then, using motorized measurements on static tissue-mimicking phantoms, we found that on-surface speeds play a more dominant role in speckle contrast drop compared to tilt of wavefronts. We also concluded that optical properties of the medium matters when studying movement artefacts such that a measurement on an opaque surface may not be sufficient to correct for movement artefacts [17]. Then, we studied the influence of wavefront types on movement artefacts in handheld LSCI.…”
Section: Related Workmentioning
confidence: 99%